Trend Pola Asuh Orang Tua dalam Pendampingan Model Pembelajaran Blended Learning pada Masa Pandemi Covid-19 - Cindra Suryaputri Anggraeni; Nur Hidayati; Hernik Farisia; Khoirulliati Khoirulliati (JECED : Journal of Early Childhood Education and Development, 2020)
This study discusses parenting styles in assisting students’ learning with blended learning model in RA. Sunan Ampel, Pasuruan. During the Covid-19 pandemi, RA Sunan Ampel implemented a blended learning model by combining online and offline learning. This study implies descriptive quantitative approach that used questionnaire as the instruments to collect the data. The questionnaire was distributed online to 11 parents of RA students as respondents. The results showed that almost parents have a authoritative parenting style indicated by parents’ attitude in engaging children to learning while playing. Meanwhile, such parents also applied permissive parenting characterized by parents’ intervention on children’s activites and no force for children to learn. Besides that, parents with authoritarian showed that they obey strict rules and punishments when children broke the rules. Above all, such uninvolved parenting implemented during the covid-19 indicated by negligent attitude of parents in engaging students’ learning.